2015
DOI: 10.18632/oncotarget.5734
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Aldo-keto-reductase family 1 B10 by 14-3-3ε and their prognostic impact of hepatocellular carcinoma

Abstract: 14-3-3ε is overexpressed in hepatocellular carcinoma (HCC) and its expression significantly associates with a poor prognostic outcome. To uncover how 14-3-3ε contributes to the tumor progression of HCC, we investigated the potential downstream targets regulated by 14-3-3ε. We found that 14-3-3ε increases expression and nuclear translocation of β-catenin and that 14-3-3ε-induced cell proliferation is attenuated by β-catenin silencing in HCC cells. Moreover, 14-3-3ε induces aldo-keto reductase family 1 member B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…The AKR1B10 gene encodes a member of the AKR superfamily . Human AKR1B10 is reported to be overexpressed in several human cancers, including lung and liver cancers . AKR1B10 is often overexpressed in male and smoking NSCLC patients, therefore AKR1B10 has been proposed as a diagnostic marker in smokers with NSCLC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AKR1B10 gene encodes a member of the AKR superfamily . Human AKR1B10 is reported to be overexpressed in several human cancers, including lung and liver cancers . AKR1B10 is often overexpressed in male and smoking NSCLC patients, therefore AKR1B10 has been proposed as a diagnostic marker in smokers with NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . reported that increased AKR1B10 is a prognostic factor for better overall survival (OS) and less metastasis in patients with hepatic cellular carcinoma (HCC) . Yoshitake et al .…”
Section: Introductionmentioning
confidence: 99%
“…After full-text review, 12 articles were excluded. Eventually, we identi ed 11 articles published between 2014 and 2019, which were included in the nal analysis [5][6][7][8][9][10][11][12][13][14][15]. The ow diagram of the literature search is shown in Fig1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies have shown that AKR1B10 is characterized by obvious carcinogenicity and can be used as a tumor marker [4]. Recently, an increasing number of studies showed that abnormal expression of AKR1B10 is signi cantly correlated with the prognosis of certain solid tumors [5][6][7][8][9][10][11][12][13][14][15]. However, the currently available results are inconsistent, and the prognostic value of AKR1B10 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AKR1B10 can convert highly reactive carbonyl groups to less toxic hydroxyl groups to protect cells from carbonyl toxic injury, although it also participates in the activation of procarcinogens [40]. AKR1B10 possesses high enzymatic activity to reduce retinaldehyde isomers, especially all-transretinaldehyde, to their corresponding retinols [5,6], resulting presumably in a decrease of the cellular levels of retinoic acid, a signal molecule involved in cell proliferation and differentiation [41][42][43][44]. AKR1B10 has been shown to promote cell growth and survival via modulating lipid synthesis and membrane function by hindering the degradation of acetyl-CoA carboxylase-(ACCA), a rate-limiting enzyme in fatty acid synthesis, through the ubiquitination-proteasome pathway [45,46].…”
Section: Functions Of Akr1b10mentioning
confidence: 99%